Effects of integrated nutrient management on different horticultural traits in onion (Bangladesh Journal of Botany, 2025)
A field experiment was conducted to evaluate the effect of integrated nutrient management on growth and yield in onion (Allium cepa L.) under sub-tropical conditions of Himachal Pradesh. Thirteen treatments were arranged including control. Minimum days to marketable maturity, maximum plant height, number of leaves, leaf length, average bulb weight, bulb length, bulb breadth, bulb yield per plot and neck thickness were found in treatment T7. Therefore, consolidation of plant nutrients through growth promoting rhizobacteria, organic manure and inorganic fertilizer ameliorate the plant growth and development, inflate soil nutrient status and nurture sustaining crop fecundity.Bangladesh J. Bot. 54(1): 153-157, 2025 (March)